Forum młodych chirurgówIsolated aortic valve replacement vs. aortic valve replacement with CABG in elderly patients (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Introduction: With the advancing age of the population in the western world, more septuagenarians and octogenarians are becoming candidates for cardiac surgery. Age is associated with increased surgical complexity required, e.g. aortic valve replacement with coronary artery bypass grafting. The aim of the study was to evaluate clinical characteristics and outcomes of patients aged 70 years or older undergoing isolated aortic valve replacement vs. aortic valve replacement with CABG and to determine the predictors of adverse outcome. Method: Between January 2001 and December 2005, 408 patients aged over 70 underwent aortic valve replacement (AVR) with and without coronary revascularisation (CABG). 157 patients (group A) had isolated AVR, 251 patients (group B) AVR+CABG. Results: There were 82 (49%) females in group A and 77 (33%) in group B (p<0.001). Parsonnet score was higher in group B [24.24 (SD 5.8) vs. 20.3 (SD 5.9) (p<0.001)]. In group B cross-clamp time was longer [118.3 min (SD 30.3) vs. 74.3 min (SD 18.9) (p<0.001)]. Patients with AVR + CABG more frequently had stroke [13 (5.5%) vs. 0 (p<0.01)], had GI complications [26 (10.8%) vs. 9 (5.7%) (p<0.05)] and had blood transfusion [0.2 U pp (SD 0.4) vs. 2.5 (SD 3.9) U pp (p<0.001)]. 30-day mortality was higher in group B, 23 (9.1%) vs. 6 (3.8%) (p 100 min [p=0.027 (95% CI 1.008-1.124)] in group A and female gender [p=0.033 (95% CI 0.015-0.840)], poor EF [p=0.002 (95% CI 4.475-6.112)], intraoperative IABP [p=0.004 (95% CI 6.702-8.796)] and no. of grafts [p=0.042 (95% CI 1.029-4.596)] in group B as independent predictors of mortality. Conclusions: Overall mortality in our series is comparable with data from other centres. Redo, preoperative AF, long CPBT and urgent referrals were independent risk factors of mortality in the AVR group. Female gender, poor EF, no. of grafts, long CPBT and intraoperative use of IABP were independent risk factors of mortality in the AVR+CABG group.